2020
DOI: 10.1007/s12325-020-01396-w
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Persistence Between Long-Acting Injectable Versus Orally Administered Aripiprazole Among Patients with Schizophrenia in a Real-World Clinical Setting in Japan

Abstract: Introduction: Persistence with antipsychotic treatment is critical in managing patients with schizophrenia. To evaluate whether aripiprazole long-acting injection (aripiprazole oncemonthly, AOM) can contribute to longer treatment persistence compared with daily orally administered aripiprazole (OA) in real-world clinical settings in Japan, treatment persistence in patients with schizophrenia was compared between patients treated with AOM and those with OA, using a claims database compiled by JMDC Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“… 10 In Japan, where LAI antipsychotics are still underused, a real-world study using the JMDC database demonstrated patients treated with LAI antipsychotics (ie, aripiprazole) were significantly less likely to discontinue treatment than those receiving aripiprazole orally (adjusted hazard ratio: 0.54; p < 0.0001). 32 In the above studies, the mean age (range) of patients with BD who received LAI and oral antipsychotics was 36.1–38.4 years and 39.1–39.3 years, respectively, 10 , 32 which was comparable with the age group of younger BD patients in our study (ie, <30 years or 30–40 years) who had poor medication adherence. Hence, the use of LAI antipsychotics could be an alternative treatment option, especially in younger patients.…”
Section: Discussionsupporting
confidence: 72%
“… 10 In Japan, where LAI antipsychotics are still underused, a real-world study using the JMDC database demonstrated patients treated with LAI antipsychotics (ie, aripiprazole) were significantly less likely to discontinue treatment than those receiving aripiprazole orally (adjusted hazard ratio: 0.54; p < 0.0001). 32 In the above studies, the mean age (range) of patients with BD who received LAI and oral antipsychotics was 36.1–38.4 years and 39.1–39.3 years, respectively, 10 , 32 which was comparable with the age group of younger BD patients in our study (ie, <30 years or 30–40 years) who had poor medication adherence. Hence, the use of LAI antipsychotics could be an alternative treatment option, especially in younger patients.…”
Section: Discussionsupporting
confidence: 72%
“…Among British cohorts of patients beginning LAI treatment, discontinuation rates at 1 year were 35-40% for paliperidone once monthly [29][30][31] and 68-55% for risperidone LAI [32,33]. Iwata et al [15] found discontinuation rates for aripiprazole of around 40% among patients with schizophrenia in Japan at 12 months of follow-up [15], whereas, in Canada, treatment retention at 18 months was 77% for a group of 70 patients with schizophrenia initiated with risperidone LAI [34]. On the other hand, in the USA, Pilon et al [35] found notably higher discontinuation rates, with more than 60% of patients with schizophrenia using aripiprazole LAI, paliperidone once monthly and risperidone LAI discontinuing treatment after 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…antipsychotics, whereas studies comparing different LAIs with each other either did not include the most recently marketed SGA LAIs or did not explore sociodemographic and clinical characteristics possibly associated with LAI adherence [14][15][16].…”
Section: Key Pointsmentioning
confidence: 99%
“…Numerous studies have also replicated the superiority of LAIs over oral APs in terms of adherence, all-cause discontinuation, rehospitalization, cost effectiveness, and functioning in the treatment of schizophrenia as well as bipolar disorder regardless of geographic regions conducted clinical trials and studies [34][35][36][37][38].…”
Section: Lais Are Better Than Oral Aps In Prevention Of Relapse and Treatment Adherencementioning
confidence: 99%
“…It is well-known that LAIs have superiority in relapse and rehospitalization over oral APs in a number of clinical trials and meta-analysis [34][35][36][37][38] despite some debates on this issue [39] due to diverse possible biases such as study methodology, expectation bias, natural illness course, and time effect [40]; indeed, the superiority of LAIs over oral APs were not found in some randomized and con-trolled clinical trials (RCTs), while LAIs were superior to oral APs in most mirror-image and some large cohort studies, indicating a mandatory change on study design in consideration of formula difference. A possible solution would be the implementation of a practical effectiveness trial in which post-randomization involvement should be kept to a minimum for better reflection of routine practice [40].…”
Section: Lais Are Better Than Oral Aps In Prevention Of Relapse and Treatment Adherencementioning
confidence: 99%